2021
DOI: 10.1029/2021je006863
|View full text |Cite
|
Sign up to set email alerts
|

YORP Effect on Asteroid 162173 Ryugu: Implications for the Dynamical History

Abstract: The Hayabusa2 spacecraft arrived at the target asteroid in June 2018 and started its homeward journey to Earth in November 2019 after an approximately 17-month asteroid-proximity phase. The capsule container with the sample from Ryugu was delivered to Earth in December 2020. The mission included two successful touchdowns to sample the surface material, an artificial cratering experiment, and deployments of a lander and rovers. Hayabusa2 revealed the nature of the rocky surface and its spinning-top shape (Watan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…Similar YORP differences for shape models of different (but very high) resolution have also been observed in simulations of asteroid Itokawa (Scheeres et al 2007). Ryugu's accelerations obtained by Kanamaru et al (2021) correspond to the non-dimensional torque τ ω of the normal YORP in the range from −0.00014 to −0.0021. The tangential YORP τ ω ≈ 0.01 derived from our model can surpass this value, causing a positive net acceleration despite the negative YORP produced by the asteroid shape asymmetry.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar YORP differences for shape models of different (but very high) resolution have also been observed in simulations of asteroid Itokawa (Scheeres et al 2007). Ryugu's accelerations obtained by Kanamaru et al (2021) correspond to the non-dimensional torque τ ω of the normal YORP in the range from −0.00014 to −0.0021. The tangential YORP τ ω ≈ 0.01 derived from our model can surpass this value, causing a positive net acceleration despite the negative YORP produced by the asteroid shape asymmetry.…”
Section: Resultsmentioning
confidence: 93%
“…( 34), we obtain the non-dimensional TYORP produced by the surface roughness on Ryugu equal to τ ≈ 0.01. Kanamaru et al (2021) uses the shape model of Ryugu revealed by Hayabusa2 to compute the normal YORP. The resulting acceleration is negative and lies in the range −0.42 × 10 −6 deg day −2 to −6.3 × 10 −6 deg day −2 .…”
Section: Resultsmentioning
confidence: 99%
“…We performed thermophysical simulations using the AsteroidThermoPhysicalModels.jl library, one of the functionalities of the asteroid dynamical simulator Astroshaper (https://github.com/ Astroshaper). This package was originally developed to predict the YORP effect on asteroid 162173 Ryugu, a target asteroid of Japan's Hayabusa2 spacecraft (Kanamaru et al 2021). The thermophysical model, originally formulated for a single asteroid, has been generalized to include all relevant thermal effects in a binary system.…”
Section: Comparison With Numerical Simulationmentioning
confidence: 99%
“…Here parameters and the magnitude of the TYORP (e.g., the size distribution and the thermal parameter of boulders) follow the research performed on asteroid Itokawa (Ševeček et al 2015). The TYORP torque differs from one asteroid to the next because the morphology of asteroids differs (Kanamaru et al 2021). For the CYORP torque, other parameters apart from the obliquity were set to be constant as δ = ∆ = α = π/4 and R 0 /R ast = 1/3.…”
Section: Order Of Magnitudementioning
confidence: 99%
“…Recently, in situ observations by spacecraft provided highresolution images of asteroids and measurements of their physical properties (e.g., Hirata et al 2009;, which enabled investigating the YORP effect with a high-resolution shape model of the considered asteroid (Kanamaru et al 2021;Roberts et al 2021). With high-resolution images, the thermally induced torque of craters whose sizes are above the image resolutions can be well represented by the NYORP torque, but we still miss the consideration of small craters or concave structures that are below the image resolution.…”
Section: Calculation Of the Total Yorp Torquementioning
confidence: 99%